OPTIMALISASI FAN PADA SISTEM VENTILASI TAMBANG BAWAH TANAH AREA KUBANG KICAU PT. ANEKA TAMBANG TBK, UBPE PONGKOR BOGOR, JAWA BARAT - Wahyu Bagas Yuniarto,; R. Andy Erwin Wijaya,; Hidayatullah Sidiq, (ReTII, 2020)
PT. Aneka Tambang TBK UBPE Pongkor contain of a few minesite. One of that stil running of production is Tambang Kubang Kicau. Needed of fresh air at Tambang Kubang Kicau up to 35.59 m3/s with 21 total of reticulation of fan that spend 1033 kW of power. Many fan that being used at Tambang Kubang Kicau causes by less maintenance of the fans, flexible ducts are break, until mistake of flexible ducts placement,. Repair plan of flexible ducts are done by changing changing flexible ducts and repairing placement so it is neither coinciding nor slicing. For making work more efficience from flexible ducts, at the adjacent mine front can be used a regulator at the flexible duct for setting the airway. At the unuse mine front can be closed by a bulkhead. After the repairment of the mine ventilation system, then amount of fans can be reduced because of fans work more optimal. Amount of the fans after repairment are 17 with 835 kW of the total power. Debt of the fresh air inside of the Tambang Kubang Kicau reach 137 m3/s and the debt of the fresh air at the mine front reach 5.1 m3/s – 6.5 m3/s.